Optimalisasi Proses Produksi Kerajinan Batik Kampoeng Batara Banyuwangi - Patrisia Mintje, Quirina Ariantji; Rumani, Daniel Dewantoro; Setiawan, Ariyono; Qiram, Ikhwanul (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2022)
Abstract – Batik is one of the arts and crafts products that are full of customs and culture of the people in Indonesia. The batik art of Kampoeng Batara UKM has existed and developed in the last two years. The limitations of technical facilities are an obstacle to batik production on a mass scale. Through this community service activity, technical support is provided in the form of production facilities for dyeing, boiling and washing media for batik cloth in the form of 10 drums with a capacity of 200 liters. Some of the drums are modified according to production needs with the capacity required by partners. The results of the activity show that the provision of technical support has given partners confidence to increase the capacity of batik products on a larger scale. Keyword: BBatik; Kampoeng Batara, Production, Technical Facilities.